2016
DOI: 10.3892/ol.2016.5446
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of recombinant human endostatin treatment on differentiated and undifferentiated blood vessels in Lewis lung cancer

Abstract: In the present study, we evaluated the effects of recombinant human (rh-)endostatin treatment on differentiated and undifferentiated tumor vasculature in Lewis lung cancer for the first time. Lewis lung carcinoma models were established. The animals were treated daily with varying doses of rh-endostatin or physiological saline for 14 days. Intravital microscopy was performed following treatment. The expression of CD31 and CD34 was determined by immunohistochemical staining, and microvessel density (MVD) was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…During angiogenesis, a balance between the activation of pro‐angiogenic genes and the inhibition of inhibitory factors stimulates angiogenesis 44 . The von Willebrand factor (vWF) gene is involved in coagulation and assists in platelet adhesion, promoting haemostasis 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During angiogenesis, a balance between the activation of pro‐angiogenic genes and the inhibition of inhibitory factors stimulates angiogenesis 44 . The von Willebrand factor (vWF) gene is involved in coagulation and assists in platelet adhesion, promoting haemostasis 45 .…”
Section: Resultsmentioning
confidence: 99%
“…During angiogenesis, a balance between the activation of proangiogenic genes and the inhibition of inhibitory factors stimulates angiogenesis. 44 The von Willebrand factor (vWF) gene is involved in coagulation and assists in platelet adhesion, promoting haemostasis. 45 As shown in Figure 4D, the expression of the vWF gene was elevated by more than 1.7-fold in the PF-127@P50 hydrogel extract group compared to the group without pectolinarin, and enhanced expression of the vWF gene was observed in all pectolinarin-treated groups except for PF-127 hydrogels alone.…”
Section: Activation Angiogenesis-related Genesmentioning
confidence: 99%
“…Vascular normalization is accompanied by CD31 (a sensitive marker of blood vessels, expressed in all blood vessels) downregulation. [51][52][53] For the tumors treated with free Ce6based PDT, the blood vessel density based on anti-CD31 immunohistochemistry (IHC) increased significantly compared to that of the NS group (Fig. 3f and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Another study found that recombinant human vascular endothelial growth inhibitor significantly reduced the number of CD31+ but not CD34+ vessels in a mouse model of lung cancer, suggesting that the immature microvessels can be inhibited by endostatin. [27] Our study analyzed the clinical data of 30 patients with advanced NSCLC who were treated with anlotinib. The tumoral vasculature was stained for CD31 and CD34.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lung adenocarcinoma of high undifferentiated-vessel MVD were more sensitive to bevacizumab [6] . Another study found that recombinant human vascular endothelial growth inhibitor significantly reduced the number of CD31+ but not CD34+ vessels in a mouse model of lung cancer, suggesting that the immature microvessels can be inhibited by endostatin [27] …”
Section: Discussionmentioning
confidence: 99%